BUDAYA ADAT PENGANTIN MELAYU RIAU DALAM PENGEMBANGAN BUDAYA KEWARGANEGARAAN - Malasari, Yosi; Darmawan, Cecep (Faculty of Humanities, Diponegoro University, 2017)
This research aims to find out how the description of the indigenous culture of bride Malay Ujungbatu Riau in the civic culture’s development. Bride Malay Ujungbatu’s Indigenous culturein the development of civic culture explores and examines the bride indigenous. The results this research show that a) the bride custom culture of Malay Ujung Batu has a culture that are: menjalang mamak, kampung suku, kampung penghulu and menjalang mintuo. In the context of civic culture, there is the value of silaturrahim, religious, family, responsibility, deliberation, and togetherness, b) the procession of bride Malay Ujung Batu includes: antar tanda, khatam Al-qur’an, tepung tawar, berinai, ber-arak or ber-dikie. In the context of civic culture, there is the value of belief, attitude, ability of cooperation, solidarity, togetherness, responsibility, mutual cooperation, c) the civic culture’s developmentas the part of civic education (PKn) takes place naturally in the family and society. The research subjects are indigenous figure, youth and society. The efforts made in preservation are motivating simultaneously from both the indigenous figure and the parents in a family environment. It can be concluded that there are civic cultural values in the indigenous of bride Malay Ujungbatu Riau as part thecivic culture’s development.